INFLUENCE OF LOW POSITIVE TEMPERATURES ON ANATOMICAL CHARACTERISTICS JUGLANS REGIA L. IN VITRO MICROCLONES - Terletskaya, N.V.; Yerbay, M.; Shadenova, E.A.; Korbozova, N.K.; Nazarova, I.; Litvinenko, Ju.A.; Kudrina, N.O. (Eurasian Journal of Applied Biotechnology, 2023)
Walnut (Juglans Regia L.) is a promising plant for use in modern medicine. We describe the reactions of Juglans Regia L. microclones exposed to cold stress in vitro at the cell and tissue level. Differences in the water content of plant tissues and the anatomical and morphological structure of the stem and leaf of Juglans Regia L. microclones under control and stress conditions are shown. Significant changes in the anatomical parameters of various stem tissues, both upward and downward, and a tendency for the values of the anatomical parameters of the leaf to decrease under cold stress conditions were revealed. It has been suggested that changes in the anatomical characteristics of organs and tissues of Juglans Regia L. microclones may affect the phytochemical content of biologically active substances in them, valuable for pharmacy.